Implementasi Kebijakan Pengelolaan Kawasan Konservasi di Kecamatan Ciracap Kabupaten Sukabumi Jawa Barat - Lubis Habibullah; Suwaib Amirudin; Nikki Prafitri (Epistemik Press, 2023)
The turtle conservation area management policy is the basis for efforts to protect turtle populations that are threatened with extinction. Turtle as a protected animal, its population is important to be protected from extinction. The turtle conservation program has an important role in the management of turtle conservation as a means of achieving turtle sustainability and supporting community life. Through this policy on the management of the turtle conservation area, the Provincial Government and its working staff carry out conservation activities at Pangumbahan Beach, which is the locus of the research. The purpose of this study was to determine how the management of the conservation area in Pangumbahan Beach. Researchers used qualitative methods. The selection of research informants used purposive sampling and snowball techniques. This study uses the theory proposed by Van Metter and Van Horn consisting of 6 aspects, namely: Policy Objectives and Measures, Resources, Characteristics of Implementing Agents, Attitudes and Tendencies (dispositions) of implementing implementors, Communication between implementers, Economic, Social and Political Environment. The results of this study indicate that the Management of the Turtle Conservation Area on Pangumbahan Beach still has problems with the activities of the surrounding community such as fishermen who reflect light at night because it affects the landing of turtles who want to land on the coast to lay their eggs.